Sleep Disturbances in Newborns - Daphna Yasova Barbeau; Michael D. Weiss (MDPI AG, 2017)
The purpose of this review is to serve as an introduction to understanding sleep in the fetus, the preterm neonate and the term neonate. Sleep appears to have numerous important roles, particularly in the consolidation of new information. The sleep cycle changes over time, neonates spend the most time in active sleep and have a progressive shortening of active sleep and lengthening of quiet sleep. Additionally, the sleep cycle is disrupted by many things including disease state and environment, and the amplitude integrated EEG can be a useful tool in evaluating sleep, and sleep disturbances, in neonates. Finally, there are protective factors for infant sleep that are still being studied.